Cathodal tDCS improves task performance in participants high in Coldheartedness. Issue 9 (September 2016) - Weidacker, Kathrin; Weidemann, Christoph T.; Boy, Frederic; Johnston, Stephen J.
Highlights: First investigation of tDCS effects in relation to psychopathic traits. Anodal and cathodal tDCS to right dlPFC modulate response inhibition in the same manner. Positive relationship between cathodal tDCS at highest task difficulty level & Coldheartedness trait. Abstract: Objective: It is investigated whether personality-related inter-individual differences modulate tDCS effects on response inhibition. Psychopathic personality traits have been associated with a reduced ability to inhibit prepotent responses and as such it is likely that these traits may modulate the effect tDCS has on response inhibition. This study represents the first investigation into the effect of psychopathic traits on tDCS effects in the context of response inhibition, and based on previous research, the psychopathic traits Blame Externalization and Coldheartedness were elected as potential candidates for modulating tDCS effects to right dorsolateral prefrontal cortex. Methods: Eighteen healthy participants underwent tDCS stimulation (sham, anodal, cathodal) before completing a response inhibition task, the parametric Go/No-go task. This task measures response inhibition under conditions of low and high cognitive load. TDCS stimulation was applied to F4 (international 10–20 system), corresponding to right dorsolateral prefrontal cortex, for 20 min with an intensity of 1.5 mA. Analysis of covariance was performed to assess how changes in response inhibition performance across difficulty level and stimulation condition were related to individual differences in psychopathy scores as measured via the Psychopathic Personality Inventory-Revised questionnaire. Results: A positive relationship was found between greater scores on the Psychopathic Personality Inventory-Revised subscale of Coldheartedness and improvement in Go/No-go task performance after application of cathodal tDCS. This effect specifically related to the high load condition of the Go/No-go task. Conclusion: The psychopathic personality trait Coldheartedness may represent an imbalance of excitatory and inhibitory inputs to dlPFC. Improvement in functioning on inhibitory tasks after cathodal tDCS may be a result of a shift of excitatory glutamate levels to a more optimal level. Significance: The current results demonstrate the utility of tDCS as a tool to assess how differences in cortical responsivity are associated with specific personality traits. Additionally, this study represents the first investigation into the influence of psychopathic traits on tDCS effects on dlPFC, and we observed beneficial changes in response inhibition as a result of, especially, cathodal stimulation in participants scoring high on Coldheartedness.